South Indian archaeology - Kamalakar, G.; Veerender, M.; Vijaya Kumar Babu, Avadhanula (Delhi : Bharatiya Kala Prakashan, 2000)
Contributed articles.
Includes bibliographical references.
Keywords: India, South -- Antiquities